2013
DOI: 10.1128/cmr.00032-13
|View full text |Cite
|
Sign up to set email alerts
|

Update on Tick-Borne Rickettsioses around the World: a Geographic Approach

Abstract: SUMMARY Tick-borne rickettsioses are caused by obligate intracellular bacteria belonging to the spotted fever group of the genus Rickettsia . These zoonoses are among the oldest known vector-borne diseases. However, in the past 25 years, the scope and importance of the recognized tick-associated rickettsial pathogens have increased dramatically, making this complex of diseases an ideal paradigm for the understanding of emerging and reemerging infections. Several s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
1,147
7
88

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 1,201 publications
(1,370 citation statements)
references
References 463 publications
(660 reference statements)
29
1,147
7
88
Order By: Relevance
“…De Sousa et al [7] hypothesise that lizards may also be reservoirs of R. monacensis, the agent of spotted fever rickettsioses [38]. As reported in previous studies in Spain and Portugal, R. monacensis was the dominant rickettsia species in lizard ticks and infected attached I. ricinus larvae and nymphs [7,21].…”
Section: Discussionmentioning
confidence: 80%
“…De Sousa et al [7] hypothesise that lizards may also be reservoirs of R. monacensis, the agent of spotted fever rickettsioses [38]. As reported in previous studies in Spain and Portugal, R. monacensis was the dominant rickettsia species in lizard ticks and infected attached I. ricinus larvae and nymphs [7,21].…”
Section: Discussionmentioning
confidence: 80%
“…18 In the case of Rocky Mountain spotted fever, eschars are reported to be very rare; however, eschars are typical in most other spotted fevers. Eschars represent skin lesions with extensive, contiguous infection by Rickettsia spp.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally thought that the development of a localized defensive reaction is a good prognostic factor, and spotted fevers that generally induce multiple eschars in patients (for example, African tick bite fever) are milder than spotted fevers that are rarely accompanied by eschars (Rocky Mountain spotted fever). 18 Infection by R. felis in Africa was described initially by two independent teams working in Senegal and Kenya. These works identified a novel healthcare problem in Africa: acute R. felis-induced fever that mimics malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly there were reports of Amblyomma latum ticks from Python; Amblyomma exornatum ticks from monitor lizards; Rhipicephalus simus ticks from dogs (Navajas et al 2010;Reeves et al 2006;Parola et al 2013). Guglielmone et al (2014) reported ten species of ticks found in pangolins also occur in different animal hosts (classified up to family level) including mammals, birds and reptiles.…”
Section: Resultsmentioning
confidence: 99%